Danske seniorers (65+) motiver og barrierer for fysisk aktivitet - Larsen, Merete Lundby; Ryom, Knud (Scandinavian Journal of Sport and Exercise Psychology, 2022)
The proportion of older adults is increasing in Denmark. At the same time physical activity is becoming an increasingly popular arena to prevent illness, promote health and increase life quality. This case study examined older adults’ (65-75 y) motives and barriers for participation in organised physical activity. Using a single embedded case study, we collected data through semi structured interviews and observation. The theoretical framework is Ryan & Deci’s Self-Determination Theory (SDT). Results of this study indicate that informants had several intrinsic and extrinsic motives. Among the extrinsic motives were better health, absence of illness, a good retirement and complying with social norms. A number of integrated and structural motives also exist: positive experience with sports, appropriate challenges, social interaction, diverse sports activities and freedom of choice. The older adults described barriers such as: difficult to self-initiate participation in sports, health related issues and lacking experiences with sports. Furthermore, the study discusses behaviour change triggers to stimulate healthy behaviour in old age using a revised FBM-model. In addition, organised physical activity that promotes satisfaction of the psychological needs is essential for the adherence. Based on the results and discussion, implications for practice are provided through recommendations on physical activity for older adults, based on organisation, activities and recruitment. Results of this study indicate that informants had several intrinsic and extrinsic motives. Among the extrinsic motives were better health, absence of illness, a good retirement and complying with social norms. A number of integrated and structural motives also exist positive experience with sports, appropriate challenges, social interaction, diverse sports activities and freedom of choice. The older adults described barriers such as: difficult to self-initiate participation in sports, health related issues and lacking experiences with sports. Furthermore, the study discusses behaviour change triggers to stimulate healthy behaviour in old age using a revised FBM-model. In addition, organised physical activity that promotes satisfaction of the psychological needs is essential for the adherence. Based on the results and discussion, implications for practice are provided through recommendations on physical activity for older adults, based on organisation, activities and recruitment.